2021
DOI: 10.1055/s-0041-1736305
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness of Counseling for Infertile Couples on Women's Emotional Disturbance: A Randomized Clinical Trial

Abstract: Objective The psychosocial burden of infertility among couples can be one of the most important reasons for women's emotional disturbance. The goal of the present study was to investigate the effect of counseling on different emotional aspects of infertile women. Methods The present randomized clinical trial was performed on 60 couples with primary infertility who were referred for treatment for the first time and did not receive psychiatric or psychological treatment. Samples were allocated to an in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 30 publications
0
1
0
Order By: Relevance
“…When the approaches, models, and intervention systems related to infertility are examined, first of all, a model, which includes the topics of informing couples about sexuality, infertility diagnosis, and treatment, creating realistic and concrete expectations and goals, gaining the ability to cope with crisis and stress in a healthy way, applying to social support resources, instilling hope, creating alternative solutions (adoption, living a life without children), and strengthening psychological resilience, can be suggested (Clapp & Adamson, 2006;Mokhtari-Sorkhani et al, 2022;Sorkhani et al, 2022;Yılmaz & Oskay, 2015;Kaya & Oskay,2019). However, individual and group counseling sessions, including the themes generated in this study shown in Figure 9 (including infertility experience, stress factors, acquired skills, social support resources, the role of a spouse, coping skills, and belief in treatment), can be configured.…”
Section: Conclusion Discussion and Recommendationsmentioning
confidence: 99%
“…When the approaches, models, and intervention systems related to infertility are examined, first of all, a model, which includes the topics of informing couples about sexuality, infertility diagnosis, and treatment, creating realistic and concrete expectations and goals, gaining the ability to cope with crisis and stress in a healthy way, applying to social support resources, instilling hope, creating alternative solutions (adoption, living a life without children), and strengthening psychological resilience, can be suggested (Clapp & Adamson, 2006;Mokhtari-Sorkhani et al, 2022;Sorkhani et al, 2022;Yılmaz & Oskay, 2015;Kaya & Oskay,2019). However, individual and group counseling sessions, including the themes generated in this study shown in Figure 9 (including infertility experience, stress factors, acquired skills, social support resources, the role of a spouse, coping skills, and belief in treatment), can be configured.…”
Section: Conclusion Discussion and Recommendationsmentioning
confidence: 99%
“…These interventions were led by a specialized health psychologist and a midwifery counselor in eight inperson sessions for participants, organized into different cohorts, lasting a total of 16 hours (2 hours per session with two sessions per week). After the final session, the post-test was distributed and completed (15). The content of the educational intervention package was developed based on findings from similar studies (16) (Table 1).…”
Section: Mic-mac Analysismentioning
confidence: 99%
“…Para distúrbios hormonais, os medicamentos podem ser prescritos para regular a ovulação e promover a concepção. Anomalias uterinas podem ser corrigidas por meio de cirurgias cirúrgicas, melhorando as chances de implantação bemsucedida (SORKHANI et al, 2021).…”
Section: Estratégias De Tratamento Personalizadounclassified